PENGARUH PENGGUNAAN SMARTPHONE TERHADAP HASIL BELAJAR SISWA SD NEGERI 106162 KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Harahap, Fatma Dewani (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2024)
The use of smartphones in the current era of globalization has become a necessity in the community, because of the availability of feature features that facilitate daily human work, one of which is used by students because it can be a source of lessons for students and can make it easier for students to do assignments from school. From this, the problem discussed in this article is how the use of smartphones and the proper use of smartphones affect the learning outcomes of students in grade V of SD Negeri 106162 Percut Sei Tuan District, Deli Serdang Regency. This research aims to determine the effect of smartphone use on the learning outcomes of fifth grade students at SD NEGERI 106162, Percut Sei Tuan District, Deli Serdang Regency. This research is quantitative research with inferential statistical analysis of product moment correlation coefficients. The population in this study were all students of SD NEGERI 106162, Percut Sei Tuan District, Deli Serdang Regency, the sample was taken using a purposive sampling technique of 24 people. Data was collected through questionnaire and documentation techniques. Based on the results of data analysis, the author found that the "r" value of product moment df 22 at the 5% significance level was 0.423, while at the 1% significance level the "r" value obtained was 0.537. It turns out that the calculated r (which is 0.771) is much bigger than the "r" table (which is 0.423 and 0.537). Because the calculated r is greater than the "r" table, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Because there is a significant positive relationship between smartphone use and student learning outcomes.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan smartphone terhadap hasil belajar siswa kelas V SD NEGERI 106162 Kecamatan Percut Sei Tuan Kabupaten Deli Serdang. Penelitian ini adalah penelitian kuantitatif dengan analisis statistik inferensial koefisien korelasi produk moment. Populasi dalam penelitian ini adalah semua siswa SD NEGERI 106162 Kecamatan Percut Sei Tuan Kabupaten Deli Serdang, sampel diambil dengan menggunakan teknik purposive sampling sebanyak 24 orang. Data dikumpulkan melalui teknik angket dan dokumentasi. Berdasarkan hasil analisis data penulis menemukan bahwa nilai nilai “r” product moment df 22 pada taraf signifikan 5% sebesar 0,423, sedangkan pada taraf signifikan 1% diperoleh nilai “r” tebel sebesar 0,537. Ternyata r hitung (yang besarnya = 0,771) adalah jauh lebih besar dari pada “r” tabel (yang besarnya 0,423 dan 0,537). Karena r hitung lebih besar dari pada “r” tabel, dengan demikian hipotesis alternatif (Ha) diterima dan hipotesis nol (Ho) ditolak. Karena terdapat hubungan positif yang signifikan antara penggunaan smartphone terhadap hasil belajar murid.